Percepção de qualidade das escolas do ponto de vista de alunos do ensino médio - Ramos, Bruno de Souza (2015)
This study aims at evaluating the perception towards the quality of services offered by private high schools in Brazil. For this purpose, field research was conducted at four different schools: two in Rio de Janeiro, one in Belo Horizonte and one in the countryside of Minas Gerais. Such research was conducted by using an instrument known a SERVQUAL, a framework developed for assessing service quality. Target audience were 1st and 2nd year high school students and the research was carried out at the schools. 44 items were evaluated, 22 being related to students’ expectations towards the services which should be offered by the school. The other 22 items evaluated students’ perception towards the actual service offered by the school. By analyzing the results it was possible to measure the difference between the service the students expected from the schools and the one actually offered by the schools. Results show great opportunities for improvement in the services and also contribute to a better and wider understanding concerning basic education service quality.